ANALISIS PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN KOTA TERPADU MANDIRI - Setyawati, Novita Wahyu (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
This study aims to examine that transmigrant community participation in the construction of KTM is very necessary and an important part in the development of KTM development. This research is a descriptive qualitative form by combining PRA (Participatory Rural Appraisal) analysis techniques and Non Parametric Statistics. The results of this study state that the level of education, place of business, community involvement, and KTM perceptions of the level of community participation in KTM development and the field of community participation indicate the existence of a link between participation in the progress of KTM development. Keywords: service quality, price, trust, intention to purchase